The Effect of Brand Image, Positive Emotions, and Consumer Crowd on Consumer Satisfaction of NPK Liquid-Fertilizer Products: An Empirical Analysis - Silvina Agustina; Silvana Maulidah; Agustina Shinta (The University of Lampung, 2024)
Consumer satisfaction management regarding NPK liquid-fertilizer in Bojonegoro, the main fruit farming center in East Java, is crucial. This study explores brand image and organic fertilizer usage. Challenges like crowded fertilizer stores can influence consumers' positive feelings, impacting their satisfaction. The research aims to examine the correlation between brand image, positive feelings, and in-store crowd with consumer satisfaction. A quantitative explanatory research method was employed with simple random sampling. Face-to-face interviews and meticulous data analysis were also conducted. The findings are expected to offer new insights for farmers and retailers of NPK liquid-fertilizer in Bojonegoro to enhance consumer shopping experiences and ensure optimal satisfaction levels. The study's results test the relationship between brand image, positive feelings, in-store crowd, and consumer satisfaction with NPK liquid-fertilizer products in Bojonegoro. While the influence of brand image on positive feelings and consumer satisfaction is inconclusive, positive feelings and in-store crowd significantly impact consumer satisfaction. The importance of managing positive emotions and providing smooth shopping experiences to enhance consumer satisfaction is emphasized. Keywords: Brand image, Consumer satisfaction, Emotional management. NPK liquid-fertilizer, Positive feelings.